2003
DOI: 10.2166/wst.2003.0120
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mathematical model of high rate algal ponds (HRAP)

Abstract: This article presents a mathematical model to describe High-Rate Algal Ponds (HRAPs). The hydrodynamic behavior of the reactor is described as completely mixed tanks in series with recirculation. The hydrodynamic pattern is combined with a subset of River Water Quality Model 1 (RWQM1), including the main processes in liquid phase. Our aim is to develop models for WSPs and aerated lagoons, too, but we focused on HRAPs first for several reasons: Sediments are usually less abundant in HRAP and can be neglected, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 2 publications
0
20
0
1
Order By: Relevance
“…5) where T is the liquid temperature, • C. T op is the optimal temperature for maximum algae growth, • C. K is an empirical constant, • C −2 . A maximum rate is achieved at an optimal value of temperature.…”
Section: Influence Of Temperaturementioning
confidence: 99%
“…5) where T is the liquid temperature, • C. T op is the optimal temperature for maximum algae growth, • C. K is an empirical constant, • C −2 . A maximum rate is achieved at an optimal value of temperature.…”
Section: Influence Of Temperaturementioning
confidence: 99%
“…Recent advances in the modeling of phototroph-bacterial wastewater treatment systems include the development of mechanistic models for high rate algal ponds (which have a shallow raceway design) (Jupsin et al 2003), for chemostats treating inhibitory pollutants (Bordel et al 2009), and for biofilms achieving secondary effluent polishing ). Of particular interest are the models of Wolf et al ) and Jupsin et al (Jupsin et al 2003) which have been developed for wastewater-related systems and calibrated using experimental data with mixedmicrobial communities.…”
Section: Modeling Phototrophic Microorganismsmentioning
confidence: 99%
“…Of particular interest are the models of Wolf et al ) and Jupsin et al (Jupsin et al 2003) which have been developed for wastewater-related systems and calibrated using experimental data with mixedmicrobial communities. In particular, the Wolf kinetic and metabolic model (termed PHOBIA) is of interest because it includes processes for the production of extracellular polymeric substance (EPS) and internally stored polyglucose by phototrophs (Staal et al 2007).…”
Section: Modeling Phototrophic Microorganismsmentioning
confidence: 99%
“…(Banihani et al, 2009; Model based process control of algae production has been considered by some researchers and engineers (Baquerisse et al, 1999;Béchet et al, 2013;Goldman et al, 1974). But only a handful of models on biomass production in open algae cultivation system are currently available, especially considering the activity of heterotrophic bacteria (Buhr & Miller, 1983;Fallowfield & Garrett, 1985;Jupsin et al, 2003;Mesplé et al, 1996). This is in comparison with more 40 years of model development in the related field of biological wastewater treatment.…”
Section: Anaerobic Digestion and Biomethane Productionmentioning
confidence: 99%
“…Some mathematical models of these systems, including high rate algal-bacterial ponds, consider links between algae and bacteria (Buhr and Miller, 1983;Jupsin et al, 2003; with Yang (2011) even focusing on CO2 supply and utilization in these systems. Yang showed that bacterial driven carbon oxidation, albeit oxidation of supplemented organic carbon, can play an important role in supporting algal activity.…”
Section: Introductionmentioning
confidence: 99%